A project feasibility study on Salt Production - Azada, Benjamin B. (College of Engineering, 1995)
Project Venture: The venture being studied is the production and sale of Industrial-grade salt. Location: The location of the plant site and head office will be somewhere in Northern Luzon, where the yearly rainfall pattern is favorable to solar salt production, and where it is easy to supply Industrial Salt for the major salt users in Metro Manila and surrounding areas. Project's Long-Range Objectives: The project aims to produce 10,000 metric tons of 95% purity Industrial Salt using a production area of 167 hectares. Sales are expected to reach over 31 million pesos by the year 2006. It aims to supply the Caustic Soda, Textile, Toilet Soap, and Ice Plant Industries with quality salt, and to help the economy in terms of foreign exchange savings. Highlights of the Project: Industry Status - This project was conceived in response to the growing demand for Industrial Salt, which at present is being met mostly by imports. There is only one producer of Industrial Salt in the country: Pacific Farms, Inc. Project Timetable - It is expected that if the project is implemented immediately, operations will only be able to start in 1997, with at least one year needed for dike construction. Mode of Financing - The sources of funds for the project include equity from interested investors, and possibly the government through the countryside development fund. Limited financing can be obtained from banks for the purchase of equipment. Investment costs - The project will cost P188,749,836. The bulk of the cost will go into land development, while other major allocations include construction of the warehouse (P45,000,000.00) and purchases of equipment and machinery (P5,016,607). Summary of Findings: Market Feasibility - Currently, around 70-80% of the country's industry salt demand is being met by imports. The project hopes to reduce that by 5-10%. The target market will be the major salt using industries. In order to seek out and keep customers, an aggressive marketing program using direct sales, technical assistance, and advertising will be utilized. Technical Feasibility - The facility will utilize solar evaporation technology based on fractional crystallization. Harvesting will be done manually, while salt washing will be done using a screw conveyor mechanism. It is expected that 10,000 metric tons will be produced per year, with fluctuations occurring due to the weather. Financial Feasibility - Throughout the 10-year period projected, the enterprise will be profitable and will have net positive cash inflows. However, because of the large investment needed in land development, the return on assets and owners' equity ratios indicate that it will be difficult to get investors. Socioeconomic Feasibility - The project will generally be beneficial to the people, in that it will give farmers an extra source of income during the dry season when no planting or harvesting is to be done. It will also save the country some 600 thousand dollars in foreign exchange in the first year of operations, and will result in more than 3 million pesos in government revenue in the form of taxes.